Pengaruh Latihan Ladder Drill Terhadap Kememampuan Dribling Pada Siswa Ekstrakurikuler Bola Basket Di Sma Negeri 1 Lubuk Linggau (International Forum of Researchers and Lecturers, 2024)
This research aims to train the agility of extracurricular basketball students at SMA Negeri 1 Lubuklinggau in dribbling the ball, identify mistakes that are often made when dribbling basketball, and provide treatment in the form of ladder drill exercises to get better dribbling results. A total of 20 students in this extracurricular activity were trained by researchers on Wednesday, Friday and Sunday in the field of SMA Negeri 1 Lubuklinggau from 15.30 to 17.00. Data was collected using the zig-zag dribbling test, namely pre-test and post-test. The aim is to compare the initial dribbling test before being given treatment and after being given treatment. The results of the research showed that there were significant changes after being given treatment in the form of an increasing number of obstacles to overcome compared to before being given treatment. This research indicates thatthere is an influence of ladder drill training